2023
DOI: 10.1186/s13041-023-01054-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Huntington’s disease phenotype progression in male and female heterozygous FDNQ175 mice

Si Han Li,
Tash-Lynn L. Colson,
Jingwei Chen
et al.

Abstract: Huntington’s Disease (HD) is an inherited autosomal dominant neurodegenerative disorder that leads to progressive motor and cognitive impairment due to the expansion of a polyglutamine (CAG) repeat in the N-terminal region of the huntingtin (Htt) protein. The creation of HD mouse models represents a critical step in the research for HD treatment. Among the currently available HD mouse models, the zQ175 knock-in mouse line is the first to display robust disease phenotype on a heterozygous background. The newer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Other measures of anxiety-like behaviour have been observed in HD models during tasks such as open field, elevated plus maze, fear conditioning, and the light/dark choice test [6,8,10,24,25]. Notably, a recent study found no difference in total distance traveled or anxiety-like behaviour in the open field in Q175FDN mice [26]. However, this study was performed during the dark phase, thus it is possible that anxiety-like behaviour is more prominent in the light phase.…”
Section: Open Field: Manifest Q175 Mice Show Habituation Deficits And...mentioning
confidence: 99%
“…Other measures of anxiety-like behaviour have been observed in HD models during tasks such as open field, elevated plus maze, fear conditioning, and the light/dark choice test [6,8,10,24,25]. Notably, a recent study found no difference in total distance traveled or anxiety-like behaviour in the open field in Q175FDN mice [26]. However, this study was performed during the dark phase, thus it is possible that anxiety-like behaviour is more prominent in the light phase.…”
Section: Open Field: Manifest Q175 Mice Show Habituation Deficits And...mentioning
confidence: 99%